Preoperative and Postoperative Serum Immunoglobulins Levels in Colorectal Cancer of Iraqi Patients - Al-Ghurabi, Batool H.; Mousawy, Khalida M.; Al- Naseri, Sana’a (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Quantitation of serum immunoglobulins (IgG, IgA and IgM) provides useful information for the evaluation of certain cancers. Objectives:to estimate serum immunoglobulins level before and after surgery, and to shed light on the correlation of immunoglobulins with progression of CRC. Patients and Methodes. By single radial immune diffusion method IgG, IgA, IgM were estimated in 100 CRC patients preoperatively, and in 20 patients postoperatively compared with 35 patients control with ulcerative colitis (UC) and 50 healthy control. Results: The study showed significantly increased the serum IgM level in patients group preoperatively (p<0.001) compared with control group. On the other hand, no significant differences were observed in respect to the mean of IgG, IgA, and IgM after surgical excision of the tumor in 20 patients. Conclusion: These finding suggests that high level of IgM might be considered as prognostic indicator.